GPR40/FFAR1 deficient mice increase noradrenaline levels in the brain and exhibit abnormal behavior - Fuka Aizawa; Takashi Nishinaka; Takuya Yamashita; Kazuo Nakamoto; Takashi Kurihara; Akira Hirasawa; Fumiyo Kasuya; Atsuro Miyata; Shogo Tokuyama (Elsevier, 2016)
The free fatty acid receptor 1 (GPR40/FFAR1) is a G protein-coupled receptor, which is activated by long chain fatty acids. We have previously demonstrated that activation of brain GPR40/FFAR1 exerts an antinociceptive effect that is mediated by the modulation of the descending pain control system. However, it is unclear whether brain GPR40/FFAR1 contributes to emotional function. In this study, we investigated the involvement of GPR40/FFAR1 in emotional behavior using GPR40/FFAR1 deficient (knockout, KO) mice. The emotional behavior in wild and KO male mice was evaluated at 9-10 weeks of age by the elevated plus-maze test, open field test, social interaction test, and sucrose preference test. Brain monoamines levels were measured using LC-MS/MS. The elevated plus-maze test and open field tests revealed that the KO mice reduced anxiety-like behavior. There were no differences in locomotor activity or social behavior between the wild and KO mice. In the sucrose preference test, the KO mice showed reduction in sucrose preference and intake. The level of noradrenaline was higher in the hippocampus, medulla oblongata, hypothalamus and midbrain of KO mice. Therefore, these results suggest that brain GPR40/FFAR1 is associated with anxiety- and depression-related behavior regulated by the increment of noradrenaline in the brain.